2015
DOI: 10.1126/science.aaa1992
|View full text |Cite
|
Sign up to set email alerts
|

Comment on “Missing gas-phase source of HONO inferred from Zeppelin measurements in the troposphere”

Abstract: Li et al . (Reports, 18 April 2014, p. 292) proposed a unity nitrous acid (HONO) yield for reaction between nitrogen dioxide and the hydroperoxyl-water complex and suggested a substantial overestimation in HONO photolysis contribution to hydroxyl radical budget. Based on airborne observations of all parameters in this chemical system, we have determined an upper-limit HONO yield of 0.03 for the reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 15 publications
(4 reference statements)
1
34
0
Order By: Relevance
“…Also the photolysis of nitrophenols or similar compounds (Bejan et al, 2006) is meaningful only in polluted areas, where concentrations of these precursors are high. Finally, the gas-phase HONO source by the reaction of HO 2 · H 2 O complexes with NO 2 , recently postulated by Li et al (2014), could not be confirmed by the same group in simulation chamber experiments (Li et al, 2015) and is also in conflict with recent aircraft measurements (Ye et al, 2015).…”
Section: Introductionmentioning
confidence: 82%
“…Also the photolysis of nitrophenols or similar compounds (Bejan et al, 2006) is meaningful only in polluted areas, where concentrations of these precursors are high. Finally, the gas-phase HONO source by the reaction of HO 2 · H 2 O complexes with NO 2 , recently postulated by Li et al (2014), could not be confirmed by the same group in simulation chamber experiments (Li et al, 2015) and is also in conflict with recent aircraft measurements (Ye et al, 2015).…”
Section: Introductionmentioning
confidence: 82%
“…The WRF-Chem model version 3.2.1 (Grell et al, 2005;Fast et al, 2006), with the CBM-Z (Zaveri and Peters, 1999) and the MOSAIC (Zaveri et al, 2008,), was used in this study. The detailed physical and chemical schemes for the simulations can be found in Tang et al (2014).…”
Section: Model Setupmentioning
confidence: 99%
“…Recently, Li et al (2014) proposed an assumed HONO source through the reaction between NO 2 and the hydroperoxyl-water complex (HO 2 q H 2 O), and suggested that the impact of HONO on hydrogen oxide radicals (HO x ) budget could be overestimated because this source mechanism consumed HO x radicals. However, Ye et al (2015) argued that the HONO yield for the reaction above is too small (with an upper-limit yield of 0.03) to explain the observation of HONO in the study of Li et al (2014), and Li et al (2015) agreed that the reaction of HO 2 q H 2 O + NO 2 is not a significant HONO source, suggesting that HONO remains an important net OH precursor, as demonstrated by many field studies (e.g., Acker et al, 2006) and our simulations.…”
Section: P Unknown Impacts On the Budgets Of Oh Ho 2 And Romentioning
confidence: 99%
“…Other potential homogeneous sources are under discussion and review. For example, Li et al (2014) proposed an internal source of HONO that consumed nitrogen oxides, although follow up discussion and further experiments indicate the source was likely strongly overestimated (Li et al, 2015;Ye et al, 2015).…”
Section: Introductionmentioning
confidence: 99%